Resisting reform : reclaiming public education through grassroots activism - VanSlyke-Briggs, Kjersti; Bloom, Elizabeth A., 1963-; Boudet, Danielle; Ohanian, Susan (Emerald Publishing Limited : Information Age Publishing, 2015)
This book is a poignant celebration of grassroots empowerment as our contributors, people who just a short time ago thought of themselves as ordinary citizens, document their call to action when their children and their profession are on the line. Practicing teachers and parents who see the direct impact of education reform on young people and are looking for straightforward and accessible information to help them understand what is happening and acquire the tools for resistance will find direction in this text. Providing inspiration, as well as practical guidance on how to become active in reclaiming education this book covers topics including the corporate takeover of education, high stakes testing, Common Core Standards, teacher preparation, grassroots activist responses, and much more. -- Publisher's web site.